The Role of Continuity of Care Companions in Preparation For the Next Pregnancy After IUFD - Ramadhani Ayu Wiguna; Andriyanti, Andriyanti; Sofia Al Farizi (Jurnal EduHealth, 2025)
Intrauterine fetus death is a very shocking condition, both physically and emotional. TheWorldHealth Organization recommend spacing pregnancy at at least 6 months after Intrauterine Fetal Death to reduce the risk of future problems pregnancies. The use of contraception is one of the important elements in pregnancy planning to allow time for the mother to undergo a complete medical evaluation, stabilize her health condition, and get the necessary psychological counseling. Case report : In this case study, assistance was provided toMrs. VA, a 25-year-old housewife, G2P1001 with underweight and chronic energy deficiency. At 25/26 weeks of pregnancy, Mrs. VA was diagnosed with Intrauterine Fetal Death. During the postpartum period, the companion made home visits by providing support to the mother after Intrauterine Fetal Death and providing validation of what the mother felt. Husband and family also always become a support system for the mother by helping to do homework so that the mother does not do heavy activities at home. After the situation improved, the companion began to provide education and information about prepare for the next healthy pregnancy. Conclusion : Risk factors for Intrauterine Fetal Death based on cases are the state of the mother who has a lower body mass index and is included in chronic energy deficiency. Based on recommendations from the World Health Organization spacing pregnancy for at at least 6 months after Intrauterine Fetal Death. Interventions in the form of counseling, social support, and health education can help mother deal with grief and restore emotional balance and maternal identity.